2015
DOI: 10.1038/emi.2015.33
|View full text |Cite
|
Sign up to set email alerts
|

Major emerging vector-borne zoonotic diseases of public health importance in Canada

Abstract: In Canada, the emergence of vector-borne diseases may occur via international movement and subsequent establishment of vectors and pathogens, or via northward spread from endemic areas in the USA. Re-emergence of endemic vector-borne diseases may occur due to climate-driven changes to their geographic range and ecology. Lyme disease, West Nile virus (WNV), and other vector-borne diseases were identified as priority emerging non-enteric zoonoses in Canada in a prioritization exercise conducted by public health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 100 publications
(112 reference statements)
0
51
0
2
Order By: Relevance
“…Similar reports documented the extension of the habitat of the tick species Ixodes scapularis (transmit Lyme borreliosis), Amblyomma americanum (vector of Amblyomma americanum transmitted Ehrlichia chaffeensis and Ehrlichia ewingii) and Amblyomma maculatum (transmit Rickettsia parkeri, potted fever agent, and the canine a p i c o m p l e x i a n ( H e p a t o z o o n a m e r i c a n u m ) ) a n d Hemaphysalis longicornis to involve new land in North America (Eisen and Eisen 2018;Ogden and Lindsay 2016;Paddock and Goddard 2015;Sonenshine 2018). Human cases of tick-borne babesiosis were recently reported in Canada, Europe and Japan (Kulkarni et al 2015;Krause 2012, 2020).…”
Section: Tick-borne Diseasesmentioning
confidence: 99%
“…Similar reports documented the extension of the habitat of the tick species Ixodes scapularis (transmit Lyme borreliosis), Amblyomma americanum (vector of Amblyomma americanum transmitted Ehrlichia chaffeensis and Ehrlichia ewingii) and Amblyomma maculatum (transmit Rickettsia parkeri, potted fever agent, and the canine a p i c o m p l e x i a n ( H e p a t o z o o n a m e r i c a n u m ) ) a n d Hemaphysalis longicornis to involve new land in North America (Eisen and Eisen 2018;Ogden and Lindsay 2016;Paddock and Goddard 2015;Sonenshine 2018). Human cases of tick-borne babesiosis were recently reported in Canada, Europe and Japan (Kulkarni et al 2015;Krause 2012, 2020).…”
Section: Tick-borne Diseasesmentioning
confidence: 99%
“…Highly infectious diseases can spread rapidly across borders through travel or trade, and international coordination is essential to a prompt and efficient response. Public health systems must be on the alert and ready to deal with new emergencies that may arise anywhere in the world, therefore developing strategies to identify priorities for intervention measures, rational allocation of resources for research and surveillance, and preparedness planning has been the focus of a large body of research in recent years (Balabanova et al 2011, Witt et al 2011, Brookes et al 2015, Dahl et al 2015, Kulkarni et al 2015, Krause et al 2008, Matthiessen et al 2016, Ng and Sargeant 2013, Xia et al 2013, Wallinga et al 2010. At the start of its activity, the EMERGE consortium set out to develop its own strategy to prioritize pathogens for its 3-year EQAEs planning, in order to improve diagnostic capabilities.…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, the trend toward fewer Mosquito Kill Days (i.e., when daily minimum temperatures are <À5°C) and more frequent Thaw Days (i.e., when daily maximum temperature >0°C) suggests the potential for increased exposure to insect vectors and other human health risks. The emergence and spread of vector-borne diseases is complex and can involve interactions among the introduction of invasive vector species, land use change, and alterations in human behavior (Allan et al 2003, Kulkarni et al 2015, Beard et al 2016. However, numerous studies have demonstrated a linkage between milder winter temperatures and the spatial distribution of insect vectors such as the endemic blacklegged tick (Ixodes scapularis Say) that carries the Borrelia burgdorferi bacteria that causes Lyme disease (Brownstein et al 2003, Leighton et al 2012, Levi et al 2015, and the invasive Asian tiger mosquito, an important vector for dengue and chikungunya fevers and eastern equine encephalitis (Platonov et al 2008, Rochlin et al 2013, Ogden et al 2014).…”
Section: Potential Impacts On Human Communities Of the Northern Forestmentioning
confidence: 99%